2008
DOI: 10.1111/j.1364-3703.2008.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the sweet orange interaction with the citrus canker pathogensXanthomonas axonopodispv.citriandXanthomonas axonopodispv.aurantifolii

Abstract: Xanthomonas axonopodis pv. citri (Xac) and Xanthomonas axonopodis pv. aurantifolii pathotype C (Xaa) are responsible for citrus canker disease; however, while Xac causes canker on all citrus varieties, Xaa is restricted to Mexican lime, and in sweet oranges it triggers a defence response. To gain insights into the differential pathogenicity exhibited by Xac and Xaa and to survey the early molecular events leading to canker development, a detailed transcriptional analysis of sweet orange plants infected with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 133 publications
(154 reference statements)
7
78
0
11
Order By: Relevance
“…In the interaction with the virulent isolate, up-regulated genes involved in cell cycle, growth and differentiation (and related with hyperplasia and hypertrophy) were identified, as has been previously described (Cernadas et al, 2008).…”
Section: The Avirulent Xcc a T Elicits A Distinct Gene Expression Patsupporting
confidence: 56%
See 2 more Smart Citations
“…In the interaction with the virulent isolate, up-regulated genes involved in cell cycle, growth and differentiation (and related with hyperplasia and hypertrophy) were identified, as has been previously described (Cernadas et al, 2008).…”
Section: The Avirulent Xcc a T Elicits A Distinct Gene Expression Patsupporting
confidence: 56%
“…One of the primary roles of SNARE proteins is to mediate fusion between cellular transport vesicles and the cellular plasma membrane for exocytosis. A study using inhibitors of vesicle trafficking has shown that this inhibition delays pustule development induced by Xcc in sweet orange Pera leaves (Cernadas et al, 2008), so the suppression of this gene would be consistent with the lack of symptoms in Xcc A T inoculated leaves. In conclusion, unlike the virulent type, the avirulent isolate Xcc A T did not prevent the development of physical barriers, such as starch accumulation or cell wall thickening, both events associated with plant defense mechanisms.…”
Section: The Avirulent Xcc a T Elicits A Distinct Gene Expression Patmentioning
confidence: 88%
See 1 more Smart Citation
“…According to the literature, 28,29 Xac induces gene transcription related to resistance, defense and response to pathological stress induced by alkaloids, terpenes and volatile compound production. However, during lesion development, there is a suppression of the defensive responses and the mobilization of nutrients toward infection sites.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Xac decreases biosynthetic rates 30 and protein catabolism, 28 whereas carbohydrates are considered signals of metabolism regulation, development and stress response. 31,32 Moreover, the production of these compounds was practically stopped with infection, which may be associated with the supply of energy required for metabolism reactions important for defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%